2011
DOI: 10.3174/ajnr.a2396
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Wall Thickness and Leukoaraiosis: Preliminary Results Using Multidetector Row CT Angiography

Abstract: BACKGROUND AND PURPOSE:LA is a condition caused by chronic cerebral ischemia and it represents an independent risk for stroke. The purpose of this work was to determine whether CAWT studied by using MDCTA is correlated with LA and its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…The data confirmed that the development of leukoaraiosis is strongly correlated with age (Saba et al, 2009). A further study showed a statistically significant correlation between increased carotid artery wall thickness and LA (and its severity) (Saba et al, 2011).…”
Section: Ischemia Cerebral Vasoreactivity and Autoregulationsupporting
confidence: 73%
“…The data confirmed that the development of leukoaraiosis is strongly correlated with age (Saba et al, 2009). A further study showed a statistically significant correlation between increased carotid artery wall thickness and LA (and its severity) (Saba et al, 2011).…”
Section: Ischemia Cerebral Vasoreactivity and Autoregulationsupporting
confidence: 73%
“…The type of the plaque is associated not only with the potential (white open arrows) on CT corresponding to the Geroulakos class 3 on US. e, f Calcified plaques (white arrowheads) on CT corresponding to the Geroulakos class 5 on US development of cerebrovascular events but also with the presence of other conditions that affect the brain such as cerebral micro-bleeds and leukoaraiosis [63][64][65].…”
Section: The Plaque Compositionmentioning
confidence: 99%
“…At our institute (Azienda Ospedaliera Universitaria di Cagliari), inclusion criteria for performing MDCTA of carotid arteries were previously published 22,23 and are as follows: presence of a sonography examination that showed a pathologic stenosis (50% of stenosis according to the NASCET criteria [22][23][24] ) and/or a plaque alteration that was considered as the presence of a heterogeneous plaque, an irregular surface, intraplaque hemorrhage, and/or the presence of ulceration in the plaque. Another criterion for performing MDCTA was identified when the ultrasound could not provide adequate information about the degree of stenosis and plaque type.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%